The Centrality of Difference in Coalition-Building across Divides: Palestinian, Israeli, and International Organizations in the Occupied West Bank. Issue 2 (1st December 2021) - Gawerc, Michelle I.
Abstract: Collective identities, as literature suggests, are constructed via an emphasis on sameness within a group and in the downplaying of internal difference. This study, however, found that collective agency, and resultingly, collective identity, was fueled just as much by a careful negotiation of difference as it was a group's core similarities. Based on interviews with Palestinian, Israeli, and international activists involved in two Palestinian-led coalitions in Israel/Palestine, the study shows how uneven privileges and other differences, could be leveraged for the benefit of the coalitions, particularly through assessing what each ethno-national group brought to the collective. When members enacted their closely negotiated and distinct roles, the coalition's sense of "we" was further solidified. Indeed, as this article illustrates, difference as well as unequal privileges, can be perceived as a defining feature of a strategically constructed collective identity and the reason for a partnership, not simply a problem to be managed.